Pemanfaatan Tumbuhan Sebagai Penyedap Rasa Alami Pada Masyarakat Suku Dayak Jangkang Tanjung Dan Melayu Di Kabupaten Sanggau - Riza Linda, Neni Juita, Irwan Lovadi, (Jurnal Protobiont, 2015)
This research aimed to find out the types of plants, benefits parts of plant organs, and processing methods used for making natural flavor. The research was carried out on the Jangkang Tanjung Dayak community in Ribau Village and the Malay community in Sungai Kosak Village, Sanggau Regency. The method used in this research was interviews with the respondents being determined through snowball sampling. Quantitative analysis was also performed by calculating the frequency of citation, percentage of habitat, and parts of the plants used as natural flavor by the communities of the two villages. The research found 7 species of plants used as natural flavor by the Jangkang Tanjung Dayak community in Ribau Village and 9 species of plants by the Malay community of in Sungai Kosak Village. The leaves were the mots commonly used parts of the two villages with a percentage of 100%. The habitat from which the plants were mostly found was in the forest and the garden. The processing method depended on the parts and types of plant used. The plants used as natural flavor had the highest citation frequency value which reached 100% of the two villages; and the lowest value in the Jangkang Tanjung Dayak community was 40% and in the Malay 25%.